PERBANYAKAN BIBIT KAKAO MELALUI TEKNIK GRAFTING, OKULASI, DAN SOMATIK EMBRIOGENESIS DI PROVINSI SULAWESI SELATAN - M Basir Nappu; Jermia Limbongan; Baso A Lologau (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
The Study of Cocoa Seed Multiplication Using Grafting, Budding and Somatic Embryogenesis inSouth Sulawesi Province. The low quality and quantity of seed is one of the obstacles to increase the cocoaproduction. Cocoa plantation revitalization program requires up to 75 million of cocoa seeds per year to supportthe development in about 200,000 hectares area. Vegetative propagation of plants such as cocoa bud grafting, sidegrafting, grafting, somatic embryogenesis (SE) can be done as one of the solutions to solve the problems. Thestudy was conducted in two cocoa-producing districts namely Luwu and North Luwu, on February to September2012. The focus of the activities was conducted research on the methods of plant propagation of cocoa that warebud grafting, side grafting, grafting, and SE which aimed to determine the most suitable method applied at the farmlevel as well as the types of clones as a source of budwood in South Sulawesi. The studies were carried out in theform of survey by selecting respondents in two locations of cocoa development. The collected data from theexperimental design were analyzed by ANOVA, and further tested was done by using Duncan’s Multiple RangeTest at the level of 5%. The feasibility of utilization of the propagation methods then analyzed using a Benefit CostRatio (B/C). The results showed that the success rate of grafting techniques and side-grafting shoots both in thenursery and in the crop ware high enough, so the seed multiplication techniques can be recommended to be appliedat the level of farmers' groups. SE seedlings technology was not recommended in smallholders, but it is possible tobe applied at private estates and national companies, that had better comprehend the application of such technologyand had adequate facilities. Local superior clones that had been identified as superior clones were Sulawesi-1,Sulawesi-2, Mocktar 01, and Buntu Batu, those were recomended to be released. Varietal released is one of majorrequirements that a clone can be developed for commercial purpose.Key words: Cocoa, propagation technology, seeds, superior clonesABSTRAKSalah satu kendala yang dihadapi dalam peningkatan produksi kakao ialah rendahnya kualitas dankuantitas bibit. Padahal, program revitalisasi perkebunan kakao memerlukan bibit kakao hingga 75 juta bibit pertahun untuk mendukung pengembangan areal seluas 200.000 ha. Perbanyakan tanaman kakao secara vegetatifseperti sambung pucuk, sambung samping, okulasi, somatik embriogenesis (SE) dapat dilakukan sebagai salah satusolusi untuk menyelesaikan permasalahan penyediaan bibit kakao. Kajian dilaksanakan di dua kabupaten penghasilkakao yaitu Kabupaten Luwu dan Luwu Utara, pada bulan Februari sampai September 2012. Fokus kegiatan ialahpengkajian terhadap metode pembibitan kakao secara vegetatif yaitu sambung pucuk, sambung samping, okulasi,dan SE yang bertujuan mengetahui metode paling cocok untuk diterapkan di tingkat petani serta jenis klon sebagaisumber entres yang digunakan di Sulawesi Selatan. Kegiatan dilakukan dalam bentuk survai dengan memilihresponden di dua lokasi pengembangan kakao. Data pengamatan dianalisis dengan menggunakan ANOVA dandiuji lanjut dengan Duncan Multiple Range Test pada taraf 95%. Untuk mengetahui kelayakan usahatanipembibitan kakao, maka dilakukan analisis Benefit Cost Ratio (B/C). Hasil kajian menunjukkan bahwa tingkatkeberhasilan teknik sambung pucuk dan sambung samping di pesemaian dan di pertanaman cukup tinggi, sehinggakedua teknik perbanyakan bibit tersebut dapat direkomendasikan di tingkat kelompok tani. Penggunaan teknologibibit SE tidak dianjurkan diterapkan di perkebunan rakyat, tetapi sebaiknya diterapkan di perusahaan perkebunanswasta dan nasional yang memiliki fasilitas yang memadai. Klon unggul lokal yang sudah teridentifikasi dapatdikembangkan yaitu Sulawesi-1, Sulawesi- 2, Mocktar 01, dan Buntu Batu. Sebaiknya klon tersebut segeradiusulkan untuk dilepas sebagai klon unggul, sehingga mempunyai legalitas sebagai klon yang dapat digunakansebagai sumber entres.Kata kunci: Kakao, teknologi perbanyakan, bibit, klon unggul